Intensive Care Infection Score – A new approach to distinguish between infectious and noninfectious processes in intensive care and medicosurgical patients. (June 2015) - Weimann, Karin; Zimmermann, Mathias; Spies, Claudia D; Wernecke, Klaus-Dieter; Vicherek, Oldrich; Nachtigall, Irit; Tafelski, Sascha; Weimann, Andreas
Objectives: Clinicians regularly encounter substantial time delays in diagnosing sepsis and administering appropriate antibiotic treatment. This study investigated the ability of the Intensive Care Infection Score (ICIS) to distinguish between infectious and noninfectious processes, and to assess the justified commencement of antibiotic therapy retrospectively, in line with hospital actual best practice and applied laboratory parameters. Methods: Intensive-care unit (ICU) patients were enrolled in this retrospective, observational study. Clinical data and laboratory parameters were determined daily. The cohort was divided into infected and noninfected patient groups. Results: Out of 172 ICU patients, including 72 postoperative patients, the predictive value for infection throughout the first 5 days in 'all patients' and the 'postoperative patient' group was highest for ICIS. An ICIS cut-off value of three could predict infection in postoperative patients with 82.9% sensitivity and 75.1% specificity. ICIS showed the lowest rate of potentially 'falsely encouraged' and 'discouraged' antibiotic therapies for noninfected and for septic postoperative patients, respectively, compared with C-reactive protein, procalcitonin and white blood cell levels. Conclusions: In the ICU, particularly for postoperative patients, ICIS is a reliable marker for the timely identification of infection. ICIS may qualify as a new decision support tool for antibiotic therapy, when interpreted within the clinical context.